PENGADAAN TANAH UNTUK PELAKSANAAN PEMBANGUNAN DEMI KEPENTINGAN UMUM (STUDI PUTUSAN NO.227/PDT/G/2020/PN.MDN) - Cindy Situmeang; Gunardi Lie; Moody Syailendra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Land Procurement for the Implementation of Development in the Public Interest is one manifestation of the social function of land rights which has been mandated in Article 6 of the UUPA. appropriate compensation for the land rights without compromising the rights and sense of justice. This includes the interests of the government as well as justice for the rights of the people taken as well as the common public interest. The research method used is a literature study that uses Court Decisions and primary & secondary sources of material as research support. The position of a person in a lawsuit complaint is also very important, in this case the judge's consideration is also needed in seeing a lawsuit, and also for the government, it must provide the right of compensation in kind. The general public upholds the basic principles of humanity and justice.